2009
DOI: 10.1371/journal.pone.0004708
|View full text |Cite
|
Sign up to set email alerts
|

Blood Stage Malaria Vaccine Eliciting High Antigen-Specific Antibody Concentrations Confers No Protection to Young Children in Western Kenya

Abstract: ObjectiveThe antigen, falciparum malaria protein 1 (FMP1), represents the 42-kDa C-terminal fragment of merozoite surface protein-1 (MSP-1) of the 3D7 clone of P. falciparum. Formulated with AS02 (a proprietary Adjuvant System), it constitutes the FMP1/AS02 candidate malaria vaccine. We evaluated this vaccine's safety, immunogenicity, and efficacy in African children.MethodsA randomised, double-blind, Phase IIb, comparator-controlled trial.The trial was conducted in 13 field stations of one mile radii within K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
249
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 276 publications
(254 citation statements)
references
References 31 publications
2
249
0
1
Order By: Relevance
“…5 AL was administered in a manner consistent with public-health practices (i.e., the first dose was given in the clinic, and the remainder was given to the parent or guardian for administration at home). However, active and passive case detection for subsequent malaria was intense and prolonged.…”
Section: Introductionmentioning
confidence: 99%
“…5 AL was administered in a manner consistent with public-health practices (i.e., the first dose was given in the clinic, and the remainder was given to the parent or guardian for administration at home). However, active and passive case detection for subsequent malaria was intense and prolonged.…”
Section: Introductionmentioning
confidence: 99%
“…To date, research in this field has focused on a few protein candidates including merozoite surface protein (MSP)-1 (14), MSP-2 (8), MSP-3 (15)(16)(17)(18), apical membrane Ag 1 (AMA-1) (19), erythrocyte binding Ag 175 (EBA-175) (20), glutamate-rich protein (GLURP) (15,21), and serine repeat Ag 5 (SERA5) (22). These Ags are all merozoite proteins, either located on the merozoite surface or contained within apical invasion organelles.…”
mentioning
confidence: 99%
“…Another Phase I trial was conducted in 135 Kenyan children of ages 12 years to 47 months, and the induced-immune response was dosage-dependent (68). However, a Phase II trial with 400 Kenyan children indicated that FMP1/AS02A may not be a promising candidate for monovalent malaria vaccine, with an overall vaccine efficacy of 5.1% only (69).…”
Section: Msp-1 In Human Trialsmentioning
confidence: 99%